Sociocultural Practices of Miscegenation in Khakassia: Marriage and Partnership Relations - Elena E. Tinikova; Anna V. Vinokurova (Oriental Studies, 2024)
Introduction. Integration serves a principal trend characterizing the dynamics of sociocultural processes in modern society, and is accompanied by progressing ethnocultural diversity, emergence of new social strata and communities, including mixed-race ones. Individual miscegenation degrees are influenced by various ethnosocial processes, primarily expanded marriage opportunities and increased interethnic unions, essentially contributed to by high migration mobility. Goals. The article seeks to outline matrimonial practices leading to interethnic unions, and attempts insights into marriage and partnership relations that dominate among mestizos (descendants of such unions) — in a regional perspective through the example of Khakassia (Russian Federation). Materials and methods. The study employs an integrated approach based on statistical data and secondary document analysis, including that of scholarly publications examining miscegenation. Survey methods (questionnaires, informal interviews) and personal observations have also proved instrumental herein. Interviews and interrogations were conducted in 2023–2024. Results and conclusions. The paper identifies some key sociodemographic characteristics of Khakassia’s mestizos, describes individual situations and related objective/subjective conditions — prior to interethnic unions and characteristic of marriage, partnership and family patterns (practices) adopted by mestizos proper and their parents. In this regard, it is noteworthy that, firstly, dating and mate choice practices are largely determined by actual environments and — the ethno-contact zone in terms of its heterogeneity or homogeneity, the latter be also contributed to by migration and urbanization. Secondly, the interviewed mestizos of Khakassia tend to focus on manifesting civil and regional identities, which results in lower ethnicity levels and somewhat relaxed attitudes to ethnic intermarriages, including for their own children. The undertaken study expands our understanding of the place and role played by miscegenation in Khakassia’s cross-cultural agenda, specifies the dynamics of interethnic unions, outlines marriage and partnership practices of mestizos. In the future, the obtained results can be used to calculate directions and prospects for the development of regional ethnosocial processes.